2007
DOI: 10.1073/pnas.0709956104
|View full text |Cite
|
Sign up to set email alerts
|

Genomic drift and copy number variation of sensory receptor genes in humans

Abstract: The number of sensory receptor genes varies extensively among different mammalian species. This variation is believed to be caused partly by physiological requirements of animals and partly by genomic drift due to random duplication and deletion of genes. If the contribution of genomic drift is substantial, each species should contain a significant amount of copy number variation (CNV). We therefore investigated CNVs in sensory receptor genes among 270 healthy humans by using published CNV data. The results in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

11
118
1

Year Published

2009
2009
2023
2023

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 139 publications
(130 citation statements)
references
References 46 publications
11
118
1
Order By: Relevance
“…Copy number variation in chemosensory receptor genes among humans has been argued to be evolutionarily neutral (Nozawa et al, 2007), raising the possibility that the sequence variants in vomeronasal receptor genes identified here may not be functionally important. However, given the strong influence of the pheromone system on rodent behavior, including aggression (Dulac and Torello, 2003), a tantalizing alternative is that one or several of these variants may influence tameness and aggression.…”
Section: Fw Albert Et Almentioning
confidence: 95%
“…Copy number variation in chemosensory receptor genes among humans has been argued to be evolutionarily neutral (Nozawa et al, 2007), raising the possibility that the sequence variants in vomeronasal receptor genes identified here may not be functionally important. However, given the strong influence of the pheromone system on rodent behavior, including aggression (Dulac and Torello, 2003), a tantalizing alternative is that one or several of these variants may influence tameness and aggression.…”
Section: Fw Albert Et Almentioning
confidence: 95%
“…Several recent studies have shown that the variation in gene number does not always result in the difference in fitness (3,6,26). In particular, random genomic drift has been shown to play key roles in the evolution of rapidly-duplicating genes, such as chemosensory receptor genes (27).…”
Section: Discussionmentioning
confidence: 99%
“…The reason for the great variation in gene number is not always clear. However, several recent studies suggest that the number of genes in a family was initially determined by their functional requirement, but after the number reached a sufficient level, the number can increase or decrease by chance (2,4,6,7).…”
mentioning
confidence: 99%
“…More recently, the variation of OR gene number was also identified among different human individuals, which is known as the copy number variation (Trask et al 1998 ;Wong et al 2007) . Interestingly, the level of interspecific divergence relative to that of intraspecific variation in OR gene copy number is not significantly different between functional genes and pseudogenes, suggesting that human intraspecific and human-chimpanzee interspecific OR gene number variations may not have any fitness consequence (Nozawa et al 2007 ;Zhang 2007) .…”
Section: The or Gene Family -The Largest Gene Family In Mammalsmentioning
confidence: 96%